Computational Studies of 4-Formylpyridinethiosemicarbazone and Structural and Biological Studies of Its Ni(II) and Cu(II) Complexes - Mydhili P. Sripathi; Sireesha Berely; Chittireddy Venkata Ramana Reddy (Heteroatom Chemistry)
To understand the stability, chelation behaviour, and biological activity of 4-Formylpyridinethiosemicarbazone (H4FPT), it is important to recognize its interactive geometry. Hence, computational studies on geometrically optimized structures of thione and thiol forms of H4FPT were performed. Binary metal complexes of the ligand, H4FPT (L) with the Ni(II) and Cu(II) metal ions (M), were synthesized and characterized by various spectroanalytical techniques as elemental analysis, molar conductance, magnetic susceptibility measurements, LC-MS, TGA, IR, UV-Visible, ESR, and powder XRD. Elemental analysis, LC-MS, and TGA studies indicate 1:2 (ML2) composition for mononuclear Ni(II) complex and 1:1 (ML) composition for dinuclear Cu(II) complex. Electronic absorption titrations, fluorescence quenching studies, and viscosity measurements suggest intercalative mode of binding of the complexes with calf thymus DNA (CT-DNA). These complexes also promote hydrolytic cleavage of plasmid pBR322. The ligand (H4FPT) and its complexes showed moderate-to-good activity against Gram-positive and Gram-negative bacterial strains. The DPPH radical scavenging studies showed antioxidant nature of both complexes.